Chronic Exercise Training Improved Aortic Endothelial and Mitochondrial Function via an AMPKα2-Dependent Manner - Chen, Xiaohui; An, Xiangbo; Chen, Dongrui; Ye, Maoqing; Shen, Weili; Han, Weiqing; Zhang, Youyi; Gao, Pingjin (Frontiers in Physiology, 2016)
Abstract Chronic exercise training is known to protect the vasculature; however, the underlying mechanisms remain obscure. The present study hypothesized that exercise may improve aortic endothelial and mitochondrial function through an adenosine monophosphate-activated protein kinase α2 (AMPKα2)-dependent manner. Ten-week-old AMPKα2 knockout (AMPKα2-/-) mice and age-matched wild-type (WT) mice were subjected to daily treadmill running for six weeks, and the thoracic aorta from these mice were used for further examination. Our results showed that exercise significantly promoted vasodilatation and increased expression and phosphorylation of endothelial nitric oxide synthase (eNOS), concomitant with increased AMPKα2 expression in WT mice. These effects were not observed in AMPKα2-/- mice. Furthermore, exercise training increased thoracic aortic mitochondrial content as indicated by increased Complex I and mitochondrial DNA (mtDNA) in WT mice but not in AMPKα2-/- mice. This may be caused by decreased mitochondrial autophagy since the expression of BH3 domain-containing BCL2 family members BNIP3-like (BNIP3L) and LC3B were decreased in WT mice with exercise. And these changes were absent with AMPKα2 deletion in mice. Importantly, exercise increased the expression of manganous superoxide dismutase (MnSOD) and catalase, suggesting that mitochondrial antioxidative capacity was increased. Notably, the improved antioxidative capacity was lost in AMPKα2-/- mice with exercise. In conclusion, this study illustrated that AMPKα2 plays a critical role in exercise-related vascular protection via increasing endothelial and mitochondrial function in the artery.